The VEGF family - Alitalo, Kari (Henry Stewart Talks, 2007)
Vascular Endothelial Growth Factors (VEGF), Inhibition of VEGF action to control tumor angiogenesis, VEGFs and VEGF receptor tyrosine kinases, Structure of VEGF, Signaling through a receptor tyrosine kinase, Role of VEGFR-1 in angiogenesis, Biological role of VEGF, VEGF in embryonic angiogenesis, Role of VEGF in physiological angiogenesis both during development and in the adult, Roles of VEGFR-3 and VEGF-C in the early phases of development, Mechanism of VEGF-C action in lymphatic development, Tumor angiogenesis, Result of overexpression of VEGF in tissues
Archived at 2018/05/31